Uncovering the relationship underlying postpartum depression and alcohol use - Kulkarni, Aishwarya. (2018)
Abstract: Postpartum depression (PPD) is an onset of a major depressive episode during the period around childbirth, affecting 5-30% of women. Epidemiological data suggests that women with a history of drug and alcohol use are more vulnerable to being diagnosed with PPD and women with PPD are more likely to relapse. In addition, evidence suggests that binge drinking by the dams may negatively impact the fetus. However, determining whether there is a direct relationship between postpartum depression and alcohol abuse is difficult to assess in the clinical population. Thus, the aim of this study is to investigate the interrelationship between postpartum alcohol use and PPD and the potential impact on offspring behavior. Given previous findings from the lab which suggested the role of HPA axis dysregulation in the development of maternal care deficits, we hypothesized that HPA axis dysregulation drives this reversible relationship. To study this, we used 2 novel genetic models of PPD that show dysregulated HPA axis function during the peripartum period. We subjected these models to a heavy binge drinking paradigm to determine whether mice exhibiting PPD-like behaviors exhibited an altered preference for alcohol (20%v/v) and how short-term alcohol exposure altered PPD-like behavior in control mice. Finally, we investigated whether binge drinking during pregnancy altered anxiety-like behavior in their offspring. Short term binge drinking altered maternal behavior in control animals at baseline and following stress, but did not disrupt normal anxiety- or depressive-like behaviors. Interestingly, all PPD and wildtype mice reduced their preference for alcohol after parturition and anxiety-like behaviors were not affected in the offspring. These findings suggest that alcohol exposure results in neural adaptation in the wildtype dams causing them to display abnormal maternal behavior.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Jamie Maguire.; Committee: Jamie Maguire, and Klaus Miczek.; Keywords: Pharmacology, Neurosciences, and Behavioral sciences.